A high-fidelity, fully immersive simulation course to replicate ENT and head and neck emergencies. Issue 2 (1st February 2019) - Hogg, E S; Kinshuck, A J; Littley, N; Lau, A; Tandon, S; Lancaster, J
Abstract: Background: Simulation-based training has a fundamental role in medical education as it allows the learner to gain experience managing emergencies in a safe, controlled environment. Methods: This 1-day course consisted of eight high-fidelity simulation scenarios, followed by a video-assisted debrief focusing on the technical and non-technical (communication skills, teamwork, leadership and situational awareness) aspects of managing ENT and head and neck emergencies. Results: Eight courses have run since June 2014. Post-course questionnaires demonstrated that candidates' confidence scores in managing airway and head and neck emergencies increased following completion of the course ( p < 0.0001). Conclusion: This was the first fully immersive ENT simulation course developed in the region. The learning objectives for each scenario were mapped to the ENT Intercollegiate Surgical Curriculum Programme. Feedback from the course indicated a continued demand for this style of training, leading to its inclusion in the training calendar.